Novel method for valorization of by-products from carrot discards - Clementz, Adriana Laura (2019)
Large quantities of carrots are annually discarded in different parts of the world because they do not meet market standards. Besides the economic loss to the producers, the discard poses an environmental problem. In order to decrease the environmental impact produced by carrot discards and increase the sustainability of this important primary crop, an integral process of extraction of valuable by-products from discarded carrots (ethanol, carotene and a fiber rich fraction), is proposed in this work. Three processes that differ in the quality of the product obtained, the yields achieved, the equipment used and hence the costs involved are suggested. The selected procedure allows extracting 97% of fermentable sugars, which were used as feedstock for a fermentation reactor. The concentration of bioethanol obtained after fermentation process was 28.8 g L−1. Bioethanol was subsequently used as a solvent for extraction of carotenes, thus reducing process costs. The extraction yield for carotenes was 94.2%. The composition of dietary fiber in the discards was also assessed. The soluble fiber (SDF)/insoluble fiber (IDF) ratio was 1:2.77, indicating that the fiber could be suitable for food supplementation.